Literature Review of Implementation HOTS-Based Assessment Instruments in Learning to Write Prose Fiction in Higher Education - Liza Septa Wilyanti; Urip Sulistiyo; Mukhlash Abrar; Nazurty Nazurty; Siti Fitriah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Competence in writing prose fiction is one of the writing competencies that Indonesian literature students must have. The higher-order thinking skills (HOTS) based fiction writing competency assessment instrument is something that cannot be separated from students' achievement of fiction prose writing competency. HOTS-based competency assessment is one of the measuring tools in the process of developing student writing competency. This research was a literature review research on the implementation of a HOTS-based fiction writing competency assessment instrument in higher education. This research used the PRISMA method. A search for relevant literature was carried out through Google Scholar database with the criteria being limited to articles published in Sinta 1-3 indexed journals in 2016-2023. 12 articles met the criteria and became material for analysis. The results of these findings indicated that the research related to learning to write HOTS-based fiction prose in higher education had not yet been carried out. The HOTS-based writing competency assessment instrument in higher education had only been used for general Indonesian language learning, it had not been used in the realm of literature learning. The findings of this systematic literature review recommended that there was a need for further research in the field of development, implementation, and evaluation of Indonesian literature learning assessment instruments, especially the development of HOTS-based fiction prose writing competency assessment instruments in higher education.